Clinical and Radiological Outcomes of Two Modified Open-door Laminoplasties Based on a Novel Paraspinal Approach for Treatment of Multilevel Cervical Spondylotic Myelopathy. Issue 6 (15th March 2022) - Guo, Qian; Xu, Yong; Fang, Zhong; Guan, Hanfeng; Xiong, Wei; Li, Feng
Abstract : To minimize intraoperative injury to extensor muscles, we performed two modified laminoplasties through a novel paraspinal intermuscular approach, and found both procedures with satisfied outcomes and advantages over conventional laminoplasty. Moreover, unilateral muscle-preserving procedure resulted in similar outcomes with less operation time compared to the other procedure. Abstract : Study Design: A case–control study. Objectives: The aim of this study was to evaluate the outcomes of two modified laminoplasties (LPs) based on a novel paraspinal approach for treating multilevel cervical spondylotic myelopathy. Summary of Background Data: No laminoplasty through a natural intermuscular plane mimicking Wiltse approach to minimize intraoperative injury to extensor muscles has ever been developed and studied. Methods: Ninety-two patients were enrolled, including patients treated with either modified LP and patients treated with concurrent conventional LP. Operation time, blood loss, and complications were recorded. Clinical outcomes were evaluated by VAS, JOA scores, and recovery rate. Cervical sagittal alignment was measured on cervical radiographs. Spinal canal expansion was assessed on CT scans. Cross-sectional area (CSA) and atrophy rate (AR) of cervical deep extensors were evaluated on MRI. Results: The average follow-up duration was 33.05, 31.55, 33.02, and 32.52 months, respectively in each group. Compared to concurrent conventional procedure, unilateral muscle-preserving procedure displayed similar, whereas bilateral muscle-preserving procedure showed significantly increased operation time and blood loss; each modified procedure resulted in comparable and satisfied perioperative clinical scores, spinal canal expansion while achieving significantly lower axial pain incidence, better cervical lordosis maintenance, and better deep extensor preservation. AR of deep extensors on the open side was significantly lower than that on the hinge side. Bilateral paraspinal approach demonstrated significantly better muscle-preservation on the open side and increased operation duration, with similar clinical scores, axial pain incidence, cervical lordosis maintenance, and spinal canal expansion compared to unilateral paraspinal approach. Loss of cervical lordosis was strongly correlated with AR of deep extensors. Conclusion: Paraspinal approach is a good manner to protect deep extensor muscles; the two modified LPs have similar effects on clinical outcomes. Level of Evidence: 3